Hodgkin transformation of chronic lymphocytic leukemia/small lymphocytic lymphoma - Vučić, Miodrag; Lilić, Božidar; Stojnev, Slavica; Krstić, Miljan (Vojnosanitetski pregled, 2024)
Introduction. In rare cases, chronic lymphocytic leukemia (CLL)/small lymphocytic lymphoma may transform into Hodgkin lymphoma, with about a hundred cases reported in the literature so far. We present a case of the Hodgkin variant of Richter transformation. Case report. After a one-year watch and wait period, a 60-year-old male with CLL developed B symptoms, generalized lymphadenopathy, and splenomegaly. Upon initial staging (Binet B/Rai 3), he was started on fludarabine, cyclophosphamide, and rituximab (FCR) regimen. After the third cycle of treatment, the right-sided axillary lymphadenopathy persisted and became painful, while the dimensions of the remaining organs affected by the disease decreased. Upon the finalization of the final sixth FCR cycle, the painful right-sided axillary lymphadenopathy persisted (though partially decreasing in size), with the development of local redness and swelling. A biopsy of the residual axillary node was performed, which revealed disease transformation into Hodgkin lymphoma. Upon multislice computed tomography-based staging (IV E clinical stage) and prognostic assessment (unfavorable prognosis), it was decided that the treatment be continued with doxorubicin, vinblastine, dacarbazine (AVD) regimen. The presented patient died two months after the diagnosis of Hodgkin transformation (HT) was established during the initial cycle of AVD. Conclusion. Although CLL is an indolent malignancy, in rare cases of HT, the prognosis is largely dismal. The available treatment strategies demonstrate suboptimal results, although novel immunotherapies may change the landscape of HT therapy in the near future.
Keywords: antineoplastic combined chemotherapy protocols; immunohistochemistry; histological techniques; hodgkin disease; leukemia, lymphocytic, chronic, b-cell; multidetector computed tomography; treatment outcome